Harnessing designer biotemplates for biomineralization of TiO2 with tunable photocatalytic activity. Issue 5 (1st April 2019) - Kim, Jung Kyu; Jang, Ji-ryang; Salman, Muhammad Saad; Tan, Lihan; Nam, Chang-Hoon; Yoo, Pil J.; Choe, Woo-Seok
Abstract: Biomineralization is a promising material synthesis strategy for environmentally benign production of nanostructured metal oxides. An important question is whether biomineralization can be used in the biomimetic synthesis of TiO2 with tunable photocatalytic properties that are conducive to diverse solar energy conversion applications. Here, we report the biomineralization of energy-state-modified TiO2 nanoparticles, where the critical properties closely related to their photocatalytic activity can be manipulated by tailoring the nature of the designer biotemplates. For this purpose, STB1 heptapeptide was employed as a nucleation center to induce TiO2 biomineralization. Three distinctive types of biomolecules (peptide, protein, and phage) were deliberately designed to contain the STB1 nucleation core at different local densities and intermolecular distances. The degree of substitutional nitrogen-doping and the morphology are all subject to the context-dependent differential availability of STB1 in the biomineralization milieu. Phage-induced biomineralization results in TiO2 with modified energy state and wire-like network morphology, which account for significantly enhanced charge dissociation/transport performance and high photocatalytic activity. This is the first study to report that a specific peptide with biomineralizing activity exerts differential impacts on the properties of resulting biomineralization products in a context-dependent manner, and will provide a powerful new strategy for tailoring of material properties via biomineralization. Graphical abstract: fx1 Highlights: Biomimetic synthesis of TiO2 with tunable photochemical properties. Deliberately designed peptide, protein, and phage to contain the STB1 nucleation core. Synchronized control of size, morphology, and substitutional nitrogen-doping. Modification of the energy states for efficient photocatalytic activity.